An effort in increasing the use of natural resources around southern coast of Yogyakarta, A case-study of coastal area of Baron, Kukup, and Krakal - KUSUMO WINARNO; MOESO SURYOWINOTO (ALM); DJALAL S. TANDJUNG (Biodiversitas Journal of Biological Diversity, 2003)
The coastal area of Baron, Kukup, and Krakal in the southern coast of Yogyakarta is an arid and dried area, and marginalagriculture land. The potential vegetation resources only live on the lands that produce cassava, corn, peanut, and soybean. The increasing benefits of sea products such as fishes still need to be invented. The aims of this research are to inventories and to increase the use of disadvantage resources. This research was conducted from October 1995 to March 1996. The result invents 70 species of useful plants and 21 species of weed that can be used by the people for the needs of their own households. The remainder products of Anona squamosa L., which might easily rot and until now unprofitable, could be used to make some jam. Phylantus emblica L. can be put into a useful product by making them to become candies. Another natural resources that are neglected are the cattle excrement and sharkskin. All kind of sharkskinâ€™s can be manufactured into leather products. While cattle excrement can be produced methane for cooking and lighting. There are 163 species of ornamental fishes in Kukup, and 20 species of consumed fishes in Baron. In search of ornamental fishes, the fishermen have a bad-habit of using hazardous materials such as potassium cyanide. Besides endangers the reef communities, algae and fish-larvae, it makes the ornamental fishes they caught unhealthy and cannot be exported since their lifespan is very short. Due to this factor, ornamental fishes are only available in the local market of Kukup.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: natural resources, waste, coast, Baron, Kukup, Krakal, Yogyakarta